THE INFLUENCE OF BRAND EQUITY ON CONSUMER PURCHASE BEHAVIOUR WITH SPECIAL REFERENCE TO MERINO LAMINATES, CHENNAI - Vinotha Rajan, Maria Alexina; G, Lawrence (The journal of contemporary issues in business and government, 2022)
This Report examines the “ The Impact of Brand Equity on Consumer Purchasing Behaviour at Merino Laminates” Consumer behavior involves the psychological processes that consumers go through in recognizing needs, finding ways to solve these needs, making purchase decisions (e.g., whether or not to purchase a product and, if so, which brand and where), interpret information, make plans, and implement these plans. Consumers often buy products not because of their attributes per se but rather because of the ultimate benefits that these attributes provide, in turn leading to the satisfaction of ultimate values. The results have been analysed and interpreted using SPSS software and the following statistical tools, Oneway Anova, Correlation, and Multiple Regression.